Pengaruh Physical Evidence Terhadap Keputusan Berkunjung Pada Café Okinawa di Kecamatan Makale - Rivaldo Ridson; Astriwati Biringkanae; Lisa Kurniasari Wibisono (Transformasi: Journal of Economics and Business Management, 2024)
This study aims to determine the effect of physical evidence on the decision to visit Okinawa cafes. This research is a quantitative descriptive research that aims to analyze and describe the effect of physical evidence. The population in this study are the owners and visitors of Okinawa cafes. The research conducted was to collect data related to the variables studied through literature research and field research. The data collection technique used is a questionnaire. The data testing techniques carried out included conducting instrument quality tests, classical assumption tests, simple regression tests and hypothesis testing. The results showed that the influence of physical evidence on the decision to visit Okinawa cafes based on the results of the determination test (R2) was 20.7%.